Functional rational expectations equilibria in market games - Jamsheed Shorish (Institute for Advanced Studies (IHS), 2006)
The rational expectations equilibrium has been criticized as an equilibrium concept in market game environments. Such an equilibrium may not exist generically, or it may introduce unrealistic assumptions about an economic agent's knowledge or computational ability. We define a rational expectations equilibrium as a probability measure over uncertain states of nature which exploits all available information in a market game, and which exists for almost all economies. Furthermore, if retrading is allowed, it is possible for agents to compute such a 'functional rational expectations equilibrium' using straightforward numerical fixed point algorithms.
Keywords: G12; D83; C63; 330; market game; rational expectations equilibrium; Bayesian updating; learning; computation; Rationale Erwartung; Bayes-Statistik; Capital Asset Pricing Model; Spieltheorie